2017
DOI: 10.1152/jn.00506.2016
|View full text |Cite
|
Sign up to set email alerts
|

Novel channel-mediated choline transport in cholinergic neurons of the mouse retina

Abstract: Choline uptake into the presynaptic terminal of cholinergic neurons is mediated by the high-affinity choline transporter and is essential for acetylcholine synthesis. In a previous study, we reported that P2X purinoceptors are selectively expressed in OFF-cholinergic amacrine cells of the mouse retina. Under specific conditions, P2X purinoceptors acquire permeability to large cations, such as -methyl-d-glucamine, and therefore potentially could act as a noncanonical pathway for choline entry into neurons. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…In HEK293T cells expressing P2X 2 receptors, we previously reported that the application of ATP opened P2X 2 receptors, resulting in the extracellular influx of choline into the intracellular space [ 27 ]. In the present study, to clarify whether choline that enters through the P2X 2 receptor is used for ACh synthesis, we applied ATP to ChAT‐HEK293 cells in choline‐rich solution to maximize choline influx and the opportunity for ACh synthesis (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In HEK293T cells expressing P2X 2 receptors, we previously reported that the application of ATP opened P2X 2 receptors, resulting in the extracellular influx of choline into the intracellular space [ 27 ]. In the present study, to clarify whether choline that enters through the P2X 2 receptor is used for ACh synthesis, we applied ATP to ChAT‐HEK293 cells in choline‐rich solution to maximize choline influx and the opportunity for ACh synthesis (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It may be explained by competition between Na + and choline + at the cation channels of P2X 2 receptors, similar to the anomalous mole fraction effects reported in Ca channels [ 32 , 33 , 34 , 35 , 36 ]. The permeability of choline + to the P2X 2 receptor is less than that of Na + [ 27 ]. We observed a significant increase in [ACh] i in choline solution because choline + freely permeates the cation channel of P2X 2 receptors without competition from Na + (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas this finding by itself could suggest that RGCs engage in a protective behaviour to reduce hypoxia-associated damage and death, the reduced expression levels of Glra1 , which encodes the subunit alpha-1 of the Glycine receptor (also expressed in RGCs 84 , 85 ), may instead indicate that RGC functionality and survival is compromised as a consequence of OIR and partially rescued by AFL administration. Finally, among the 10 genes associated to the chemical synaptic transmission term, P2rx2 , which encodes a subunit of a ionotropic receptor expressed in starburst amacrine cells 86 , was the most significantly down-regulated gene in OIR relative to normoxic retinas and subsequently up-regulated in response to AFL at P17. No GO terms in the biological process domain were detected as enriched in P19(AFLx2) or P19(AFLx3) retinas.…”
Section: Resultsmentioning
confidence: 99%